Strategi Pembelajaran Inkuiri: Analisis Kelebihan dan Kelemahan dalam Pendidikan - Jannah, Azizah Miftahul; Aprilia Miftah; Gusmaneli (Journal of Education and Social Culture, 2025)
Education plays an important role in shaping character and improving the quality of human resources. In the context of learning, the strategies implemented by educators have a major influence on the success of the teaching and learning process. One of the developing approaches is the inquiry learning strategy, which places students as active subjects in seeking and building knowledge through exploration and investigation. This approach supports the development of critical thinking skills and student independence, as well as strengthening learning motivation. This study aims to analyze the implementation of the inquiry learning strategy, explore the advantages and challenges faced in its implementation, and formulate an appropriate implementation strategy. The research method used is a literature study with a descriptive qualitative approach. The results of the study show that the inquiry strategy is effective in improving student learning outcomes, critical thinking skills, and social skills, but also faces challenges such as time constraints and teacher readiness. Therefore, for its optimal implementation, it is necessary to select a strategy that is in accordance with the characteristics of students and teaching materials, as well as support from competent teachers. Inquiry learning has proven to be an innovative alternative in improving the quality of education, especially in equipping students with 21st century skills.